PENGELOLAAN UNIT PRODUKSI MINI MART SMK BATIK 1 SURAKARTA SEBAGAI PENGASAH KEMAMPUAN DAGANG SISWA - Arinda Handayani; Joko Suwandi (Buletin Literasi Budaya Sekolah, 2023)
Nowadays human needs are getting higher making companies compete with each other to meet human needs and get profits. Entrepreneurship is a career that is increasingly in demand because of the greater opportunities. Because high trade competition at this time, vocational schools need to give encouragement to students' entrepreneurial abilities by forming mini mart business unit. Entrepreneurial practice is made to produce graduates with good knowledge and can compete in the business world. The mini market business unit is expected to hone students' trading skills with economic activities related to daily, buying and selling merchandise. SMK Batik 1 Surakarta believe these economic activities can foster an entrepreneurial spirit and students' interest in commerce. This study uses qualitative methods to find out the meaning of mini mart, management, and benefits for all school members. This research was conducted to find out more in-depth methods of developing trade skills of Batik students at SMK 1 Surakarta and expectations for school graduates.